2019
DOI: 10.1007/s00223-019-00621-1
|View full text |Cite
|
Sign up to set email alerts
|

Do Vitamin D Level and Dietary Calcium Intake Modify the Association Between Loop Diuretics and Bone Health?

Abstract: Loop diuretics (LD) may affect bone health by inhibiting renal calcium reuptake. However, whether vitamin D status and dietary calcium intake modify the association between LD and bone outcome is unclear. Therefore, this study aimed to evaluate whether vitamin D level or calcium intake modify the association between LD and various indices of bone health including bone mineral density (BMD) and Trabecular Bone Score (TBS). From The Rotterdam Study, a prospective population-based cohort study, we used data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…However, no association between loop diuretics and BMD was found in two other observational studies [ 265 , 266 ]. Furthermore, a population-based cohort study showed that past use of loop diuretics was associated with higher lumbar spine BMD compared to never use, while no significant association between current use and lumbar spine BMD was found [ 267 ]. However, when studying the duration of use, a positive association between current use of loop diuretics and lumbar spine BMD was found in participants using the medications for a duration of use between 121 and 365 days.…”
Section: Non-osteoporotic Medications Fracture Risk and Bmdmentioning
confidence: 99%
“…However, no association between loop diuretics and BMD was found in two other observational studies [ 265 , 266 ]. Furthermore, a population-based cohort study showed that past use of loop diuretics was associated with higher lumbar spine BMD compared to never use, while no significant association between current use and lumbar spine BMD was found [ 267 ]. However, when studying the duration of use, a positive association between current use of loop diuretics and lumbar spine BMD was found in participants using the medications for a duration of use between 121 and 365 days.…”
Section: Non-osteoporotic Medications Fracture Risk and Bmdmentioning
confidence: 99%
“…For example, thiazolidinediones demonstrate detrimental effect on the skeleton and increase fracture risk [ 545 , 599 , 600 , 601 , 602 , 603 , 604 ] but a beneficial effect on muscle atrophy [ 605 ]; other anti-diabetic drugs (sulfonylureas, metformin and possible incretin mimetics) have a neutral or a positive/protective effect on bone health, but they may increase propensity for falls through hypoglycemia (insulin and sulfonylureas) [ 601 , 603 , 604 , 606 ]. When analyzing the complex relationships between OFs and drugs used it should also be taken into account that many medications (corticosteroids, sulfonamides, urea derivatives, vitamin K antagonists, cardiac glycosides, loop diuretics, potassium-sparing diuretics, ACE inhibitors, serotonin reuptake inhibitors, calcium-channel blockers and antiepileptic drugs) may affect the vitamin D status and calcium homeostasis [ 607 , 608 , 609 , 610 , 611 ]. Importantly, even in diseases inversely associated with HPI the abovementioned drugs may contribute to OP and/or falls and should be used with caution, especially in individuals with high fracture risk.…”
Section: Hpi-associated Chronic Extra-gastroduodenal Diseases Medmentioning
confidence: 99%
“…An adequate dietary calcium intake has been associated not only with the prevention of hypertension during pregnancy but also with the reduction of low-density lipoprotein (LDL), cholesterol levels and prevention of osteoporosis and colorectal adenomas ( Cormick and Belizan, 2019 ). However, the benefits of calcium supplementation on bone health seem to be greater in children and adolescents with higher needs of calcium intake ( Oliai Araghi et al, 2020 ). Owing to the serious consequences of hypertension in pregnancy, several studies have targeted to decrease the development of pre-eclampsia in pregnant women during their first couple of weeks of pregnancy.…”
Section: Resultsmentioning
confidence: 99%